PERAN KOMUNIKASI BENCANA TERHADAP MITIGASI GEMPA BUMI DI SMK MEGA BANGSA - Taqwa Putra Budi; Anindya Putri Pradiptha; Justin Bongsoikrama; Jeremy Putra Pratama; Dinda Ramadhanty Niigata (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The increasing intensity of disasters in Indonesia today has become a priority issue that is considered not only by the government but by the academic community to the media The purpose of disaster risk reduction or mitigation is to anticipate problems that will arise during a disaster, develop ways to deal with these problems effectively, and organize the resources needed for a more efficient response.The method used is qualitative research In this research, the Research Focus or Definition of Concepts that I use is by conducting FGD (Focus Group Discussion) activities. Based on the results obtained from the Focus Group Discussion (FGD), it was revealed that the communication carried out by Budi Luhur University in the disaster mitigation activity program carried out by SMK Mega Bangsa revealed that the implementation of disaster communication in the disaster mitigation program at SMK Mega Bangsa “Strongly agree if this program is implemented into the curriculum, especially the Merdeka Curriculum which is implemented throughout the school” In this program the researcher concluded that the involvement of all school members (students, teachers, and administrative staff) in the Disaster Safe Education Unit is considered important to ensure the safety of everyone in the school environment is a top priority. This study states that the role of disaster communication in the implementation of the Disaster Mitigation program at SMK Mega Bangsa is very necessary to prepare for disasters in the school environment.